Application of Building Information Modelling in Construction Projects - Mabrouka Shahat Younis Elfargani (African Journal of Advanced Pure and Applied Sciences, 2022)
In recent years, building information modelling (BIM) has been one of the most popularly debated topics in journals on technological progress in construction projects. In the construction project model that is built and applied via a collaboration network, the BIM concept incorporates all tasks related to planning, construction and operation. The paper of focus is applied risk and change management focusing on the building information modelling (BIM) from the perspective of from the point of view of the construction projects management theory and structure. However, negative affects such as setbacks and financial damages to the detriment of participants' public projects, in particular, pose a concern as to whether and how the application of BIM standards will enhance management practices in the context of construction projects correlated with risk. This paper aims to deal with the current situation of building projects, information about risk and change management in the construction project, as regards the application of BIM, and to guide further studies. The arguments highlighted in this paper are using in the analysis of many reference kinds of literature. However, the risk is a subject that should always be established in the concept of BIM. An effective way to combine risk construction projects processes, practises and strategies with other management actions for construction projects within BIM must be created. Moreover, change is considered one of the main factors in risk and the incorporation into this framework of change management processes includes the introduction of guidelines and methodological approaches within BIM. In addition to that studies on this field includes previous expertise in implementing BIM in construction programmes, the involvement in this point of risk-related processes and requirements for successful coordination of management.